2022
DOI: 10.1093/jxb/erac183
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and responses to climate change of biocrust-forming mosses in drylands

Abstract: The interest in understanding the role of biocrusts as ecosystem engineers in drylands has substantially increased during the last two decades. Mosses are a major biocrust component that dominate its late successional stages. In general, their impacts on most ecosystem functions are greater than those of early-stage biocrust constituents. However, it is common to find contradictory results regarding how moss interactions with different biotic and abiotic factors affect ecosystem processes. This review aims to:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 179 publications
0
19
0
Order By: Relevance
“…4A). For dark mixed BSCs, which are more sensitive to aridity (Reed et al 2012, 2019, Maestre et al 2015b, Tamm et al 2018, Ladrón de Guevara and Maestre 2022), the spatial component of greatest variance is cover (Fig. 3B,E), which is likely negatively affected by aridity (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…4A). For dark mixed BSCs, which are more sensitive to aridity (Reed et al 2012, 2019, Maestre et al 2015b, Tamm et al 2018, Ladrón de Guevara and Maestre 2022), the spatial component of greatest variance is cover (Fig. 3B,E), which is likely negatively affected by aridity (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Given projected increases in aridity in many drylands (Cook et al 2020, Lian et al 2021), several lines of evidence from our study suggest that high successional BSC cover will significantly decrease in coming years, consistent with many other studies (Reed et al 2012, 2019, Maestre et al 2015, Ferrenberg et al 2015, Rodriguez-Caballero et al 2018). Shading provided by vascular plants and lichens within dark-mixed BSCs may promote persistence of dark-mixed patches, however lichens are also notably susceptible to climate change and disturbance (Navas Romero et al 2020, Finger-Higgens et al 2022, Ladrón de Guevara and Maestre 2022). While we find evidence of coupled patch responses of BSCs and vegetation to stress through observational data, controlled experimentation is necessary to fully elucidate mechanisms of patch responses and ecohydrological interactions.…”
Section: Discussionmentioning
confidence: 99%
“…First, the ability of biocrust organisms to enter a state of dormancy between hydration events gives them a major advantage in withstanding long periods without moisture (Coe et al, 2014). In particular, rising temperatures and enhanced evaporation mean that many small rainfall events will soon become photosynthetically unproductive, and even deadly, while effective periods of desiccation will lengthen (Coe et al, 2012; Ladrón de Guevara & Maestre, 2022; Reed et al, 2012). Second, many biocrust taxa have a remarkable capacity to regenerate from vegetative tissues (de la Torre Noetzel et al, 2020; Stark et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Moisture variables relating to total rainfall are intended to capture the limit beyond which biocrust carbon budgets become negative, and possibly the cool‐edge limit where vascular plant competition becomes too strong. We selected an arbitrary threshold of 1 mm to capture rainfall events because the interpolated climate data rarely estimated exactly 0 mm of rainfall and very small rainfall events are often photosynthetically unproductive for biocrust organisms (Ladrón de Guevara & Maestre, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, it has been suggested but not confirmed that high-elevation habitat (e.g. mountains), north-facing slopes (in the northern hemisphere), and shade vegetation may offer an oasis to dryland mosses by reducing local extremes in temperature, incident radiation, and evaporative demand (He et al 2016, Li et al 2018, Ladrón de Guevara & Maestre 2022. Aridity is known to drive patterns in moss abundance and community composition in many drylands (Nash et al 1977, Seppelt et al 2016, Clark 2020, however no studies have tested the physiological significance and prevalence of biocrust moss habitat buffering over natural, multiscaled aridity gradients.…”
Section: Habitat Buffering May Shelter Biocrust Mosses From Climatic ...mentioning
confidence: 94%